The Effect of IFRS Adoption, Firm Performance, Audit Quality, Leverage, and Firm Size on Foreign Ownership - Maria Mathilda Putri; Agustin Ekadjaja (Graduate Program of Universitas Tarumanagara, 2023)
IFRS and IAS are internationally accepted accounting standards issued by the IASC/IASB with the aim of uniform accounting standards throughout the world. In diversifying their investments, in addition to understanding the financial statements, investors also need to understand the firm performance and audit quality to increase confidence that the investment will generate profits in the future. The purpose of this research is to determine whether the IFRS adoption, firm performance, and audit quality will significantly affect foreign ownership. The method applied to process research data is a quantitative-descriptive method with unbalanced panel data of eighteen companies registered in the manufacturing sector from 2017-2020. From the results of multiple regression analysis using SPSS, it is known that IFRS adoption has a positive and insignificant effect on foreign ownership. Meanwhile, based on the research results, it is known that the firm performance and audit quality show significant positive results on foreign ownership.